2022
DOI: 10.1038/s41388-022-02220-1
|View full text |Cite
|
Sign up to set email alerts
|

Trop-2, Na+/K+ ATPase, CD9, PKCα, cofilin assemble a membrane signaling super-complex that drives colorectal cancer growth and invasion

Abstract: Trop-2 is a transmembrane signal transducer that is overexpressed in most human cancers, and drives malignant progression. To gain knowledge on the higher-order molecular mechanisms that drive Trop-2 signaling, we applied next-generation sequencing, proteomics, and high-resolution microscopy to models and primary cases of human colorectal cancer (CRC). We had previously shown that Trop-2 induces a Ca 2+ signal. We reveal here that Trop-2 binds the cell membrane Na + /K + -ATPase, and that clustering of Trop-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(79 citation statements)
references
References 68 publications
1
74
0
4
Order By: Relevance
“…The knockdown of TROP2 showed the opposite effect and inhibited metastasis [ 28 ]. Recently, it was found that TROP2 binds to CD9 and is subsequently phosphorylated by PKCα, leading to the activation of AKT and ERK, which in turn causes β-actin cytoskeleton remodeling and tumor progression [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The knockdown of TROP2 showed the opposite effect and inhibited metastasis [ 28 ]. Recently, it was found that TROP2 binds to CD9 and is subsequently phosphorylated by PKCα, leading to the activation of AKT and ERK, which in turn causes β-actin cytoskeleton remodeling and tumor progression [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we have revealed a potentially more decisive function of TROP2 in de-adhesion of cancer cells as the starting point of metastasis. TROP2 was localized in long cell protrusions interspersing ATF2-negative cell aggregates, linking its function to the cytoskeleton machinery as recently described [ 33 ]. Such filopodia act as sensors for signals, such as chemo-attractants or nutrients.…”
Section: Discussionmentioning
confidence: 84%
“…1 , Chella A. 5 , Amoroso D. 1 , Baldini E. 4 1 Medical Oncology, Versilia Hospital, Azienda USL Toscana Nord-Ovest, Lido di Camaiore; 2 SODc Oncologia Medica -Azienda Ospedaliero Universitaria Careggi, Firenze; 3 Radiation Oncology Unit, Oncology Department, AOU Careggi, Firenze; 4 Medical Oncology, San Luca Hospital, Azienda USL Toscana Nord-Ovest, Lucca; 5 Unit of Pneumo-Oncology, Azienda Ospedaliero-Universitaria Pisana, Pisa; 6 Medical Oncology, Azienda Ospedaliera Universitaria Senese, Siena Background: Limited evidence is available concerning the efficacy and safety of chemotherapy after previous immunotherapy in advanced NSCLC patients.…”
Section: A23 Efficacy Of Chemotherapy After Immunotherapy: Results Of...mentioning
confidence: 99%
“…2 , Montanino A. 2 , Sandomenico C. 2 , Sforza V. 2 , Costanzo R. 2 , Damiano S. 2 , La Manna C. 2 , Martucci N. 2 , La Rocca A. 2 , De Luca G. 2 , Totaro G. 2 , De Cecio R. 2 , Picone C. 2 , D'Auria S. 2 , Normanno N. 2 , Pascarella G. 2 1 Istituto Nazionale Tumori, Fondazione G. Pascale,Napoli;2 Istituto Nazionale Tumori Pascale, Napoli Background: Objective of the present study was to highlight the sources of harm that could negatively impact on decision making or affect the planning process of a Lung Multidisciplinary Team (MDT), in order to define the level of risk of each factor, evaluating the likelihood and severity of harm and suggesting risk mitigation measures.…”
Section: A24 Risk Management In the Activity Of A Lung Cancer Multidi...mentioning
confidence: 99%